Science Doesn't Dictate What's "Impossible" - Braude, Stephen (Journal of Scientific Exploration, 2019)
In this issue we present commentaries on a remarkably simplistic critique of psi research published recently by Arthur Reber and James Alcock—hereafter, R&A (Reber & Alcock, 2019a, 2019b). I believe the rebuttals that follow, from Cardeña and others, effectively demolish R&A’s critique. But I also believe a few additional points are worth making. These highlight not only R&A’s ignorance of—indeed, refusal to consider—relevant data, but also their general conceptual naivete. And I’ll focus primarily on R&A’s assertion that alleged psi phenomena are impossible. Note, R&A aren’t merely making the likewise inadequate but at least superficially more sophisticated claim that psi phenomena are initially improbable relative to some well-supported background theory. But even if we were to concede that the phenomena (including small-scale ESP and PK) are initially improbable relative to an accepted background theory, we’re still not compelled to deny their reality. We need only show that the direct evidence in their favor overrides their initial and conditional improbability. That, I believe, is easy to do, but of course, R&A are fortified by their refusal to consider the data. Moreover (as some of the commentaries note), R&A greatly overestimate the level of support for what they take to be the background physical theory. In any case, the more relevant points for now are these. First, there are serious reasons for thinking that no well-supported broad scientific theory (e.g., quantum physics, or the general or special theories of relativity) precludes the existence of any specific mental phenomenon, normal or paranormal. Arguably (I think persuasively), those phenomena are simply outside the domain of physics. I’ll return to this point shortly. For that matter, the existence of ESP is compatible even with theories of perception in psychology. Of course, those theories are much more limited in scope than the grand theories of physics or (say) evolutionary theory. So even if theories of perception did prohibit the existence of ESP, the failure of that prediction would matter little to science as a whole. But in fact, those theories merely describe the operation of the familiar or known sense modalities. It’s simply not their business to legislate the full range of possible forms of information acquisition or organic interaction. So if evidence leads us to accept the existence of previously unacknowledged perceptual modalities, psychology would simply find its domain expanded.